PENGARUH THREAT EMOTION DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN TROPICANA SLIM DI KOTA SEMARANG - Fauzan Ramadhani; Bulan Prabawani (Universitas Diponegoro, 2019)
This research was conducted with the aim to determine the effect of threat emotion and brand trust on purchasing decisions. This research was conducted on Tropicana Slim products. The sample of this study amounted to 100 respondents. This study consisted of 3 variables, 13 indicators and 3 hypotheses. The analytical tool used is SPSS 25 for Windows with validity test, reliability test, correlation coefficient test, coefficient of determination, simple and multiple regression analysis, and significance test (t test and F test). The results of this study indicate that there are positive effects of threat emotion and brand trust variables on the purchase decision variable. Threat emotion variable has the biggest influence that is 0.705 while the brand trust variable has an influence of 0.567. Based on the results it is advisable for the tropicana slim to do more early diabetes awareness programs to the public.